4. Haugh Unit Value, Yolk Index And Albumin Index Of Eggs In Farms, Distributors And Retails In Banda Aceh - Andi Novita; Alingga Savira Edi Putri; Azhari Azhari; Rastina Rastina; Muttaqien Bakri; Amiruddin Amiruddin; Fadli A Gani; M Daud AK (Universitas Syiah Kuala, 2021)
This study aims to determine the quality of eggs from Farm, distributors and retail stores. The sample used is 66 eggs with details taken randomly at the farm is 9 eggs, distributors is 27 eggs and retail stores is 30 eggs. The observed egg quality is the value of Haugh unit, Yolk Index and Albumin Index. The data obtained were analyzed descriptively. The results showed that the average Haugh value of egg units in farms, distributors and retail stores were 91, 72 and 7. The Yolk Index values for eggs in farms, distributors and retail stores were 0.45, 0.35. and 0.36. Meanwhile, the albumin index of eggs in farms, distributors and retail stores was 0.074, 0.050 and 0.046. Egg quality in farms, distributors and retail stores is in the category (grade) AA (HU value 72) and A (HU value 60-72). Based on the results of this study, it can be concluded that the quality of eggs traded in Banda Aceh and its surroundings is very good (included in the AA and A grade categories).